Settlements as territory: forging the identity of the settled rural worker - Miranda, Maria Elena (Cadernos CERU, 2008)
The article seeks to approach processes of construction of the peasant identity in the Fazenda Reunida settlement, in the town of Promissão, in the west of São Paulo state. The research conducted at the settlement aimed at unravelling these processes based on analyses of the forms of appropriation of the land and of settlers' strategies for its transfer. It was thus ascertained that the sale of "rights" to plots, which took place at the settlement, strengthened the peasant identity by recreating the kinship territory, since most of these plots were bought by relatives of settlers of by the settlers themselves, with a view to passing them on to their married children. This mechanism allowed them to resolve certain land inheritance deadlocks.